“Hidden Gems” and “Rough Mannerisms”: Examining Preservice Teachers’ Discourses of Place and Rurality - Reagan, Emilie; Coppinger, Emilie; Mascio, Bryan; Tompkins, Allie; Fornauf, Beth (Theory & Practice in Rural Education, 2024)
While research has examined preservice teachers' perceptions toward rural schools, there is limited research on how they navigate their own discourses of rural communities, particularly for preservice teachers embedded in the rural communities in which they teach. In this exploratory qualitative study, we examine the discourses of place and rurality of four preservice teachers (residents) while enrolled in a rural teacher residency program in the northeastern United States. Findings suggest that rural residents' discourses oscillated between place "as it is" and place as it "ought to be" as they identified strengths and challenges of generalized and specific rural communities. Additionally, findings suggest that preservice teachers engaged with and resisted idyllic and deficit discourses of place and rurality, drawing on their experiences living in and engaging with the unique contexts of their rural communities. We offer implications of this work for our responsibility as teacher educators who prepare teachers for schools and the rural contexts in which they will teach.